Preparation and drug release properties of lignin-starch biodegradable films - OGAN, AYŞE; ÇAKMAKÇI, EMRAH; KAHRAMAN, MEMET VEZİR; KAYAMAN APOHAN, NİLHAN (WILEY-V C H VERLAG GMBH, 2012)
Starch is one of the most commonly available natural polymers which are obtained from agro-sources. It is renewable and abundant in nature. Unfortunately due to its poor mechanical properties and hygroscopic nature, there are some strong limitations to the development of starch-based products. Usually blends of starch are prepared and plasticized with glycerol to improve some of its properties. In this study, lignin was extracted from hazelnut shells and investigated as a potential additive for starch biofilms. The structural characterization of hazelnut lignin was performed by employing UV spectroscopy and Fourier transform infrared (FTIR) spectroscopy. Lignin was blended with corn starch in different ratios to obtain biofilms. Mechanical and thermal properties of the biofilms were enhanced as the lignin amount was increased in the formulations. Water absorption tests were performed at pH 2.0, 4.0, and 6.0. The percent swelling values of the starch/lignin films increased as pH increased. Also, the biofilm exhibiting the best properties was chosen for the drug release studies. Biofilms showed a fast ciprofloxacin (CPF) release within an hour and then the drug release rate decreased. A pH dependent drug release mechanism was also observed according to KoshnerPeppas model. The drug release increased with a decrease in pH.
Keywords: Ciprofloxacin; Drug release; Hazelnut; Lignin; Starch; THERMAL-DEGRADATION; KRAFT LIGNIN; BLENDS; POLYCAPROLACTONE; COMPOSITES; BIOCOMPOSITES; MORPHOLOGY